Formal mentorship and instructional practices: a Teaching and Learning International Survey (TALIS) study of US teachers. Issue 1 (13th January 2021) - Hightower, Andromeda; Wiens, Peter; Guzman, Steven
Abstract : Purpose: Within schools across the USA, mentees supported by mentors experience a number of potential benefits, including high job satisfaction, less attrition and more opportunities for professional/emotional guidance. However, these benefits are less understood in the context of formal mentorship specifically, as well as to what extent these supports apply to instructional practices. This study aims to address the minimally researched area of how being mentored might impact the instructional practices of teachers at all stages of their career. Design/methodology/approach: Based on data recently published for the Teaching and Learning International Survey (TALIS) in 2018, this study examines the relationship of teachers with formally assigned mentors, the number of total years of teaching experience and instructional practices. US teachers who responded to the target survey questions ( n = 1, 934) were submitted to several one-way analyses of variance to determine (1) the potential relationships between the presence of a formal mentor and instructional practices and (2) how different groups of teachers with varying numbers of total years of teaching experience impacted these relationships. Findings: The results found that the presence of a formal mentor predicted higher classroom management practices, clarity of instruction practices and cognitive activation activities for the combined sample ( p < 0.05), and for teachers with 15 years or more of teaching experience, the presence of a formal mentor predicted higher classroom management and clarity of instruction practices ( p < 0.05). Originality/value: The results provide evidence for the use of formally assigned mentors beyond new teacher induction, but the nature of the formal mentorships in this study is unclear. Future research should further investigate descriptive cases of more inclusive formal mentorship programs.